Pengaruh Corporate Governance, Corporate Risk Disclosure, dan Kinerja Keuangan Terhadap Nilai Perusahaan - Maria Dwirosari Irwanni; Manuel Ari Partiuran Manullang; Ben Urim; Hexana Sri Lastanti (Forum Kerjasama Pendidikan Tinggi, 2026)
Firm value is a crucial measure that demonstrates an organization's effectiveness in improving the well-being of its shareholders. In reality, a greater firm value is influenced not just by financial performance but also by corporate governance practices and the transparency of risk disclosures. The aim of this study is to investigate the effects of independent commissioners, audit committees, institutional ownership, coporate risk disclosure, and financial performance on the value of basic material companies listed on the Indonesia Stock Exchange. Using secondary data collected from business annual reports for the years 2023–2024, this study uses a quantitative method. The sample for the study includes 91 companies, resulting in 182 observations, chosen through purposive sampling. Additionally, the data was analyzed using panel data regression with the help of EViews software. The novelty of this study is using the most recent data from the basic materials industry, this research focuses on integrating corporate governance, corporate risk disclosure, and financial performance indicators into a single research model. The findings indicate that institutional ownership and corporate risk disclosure affect firm value, while independent commissioners, audit committees, and financial performance do not affect firm value. Thus, this study can be a useful tool for business management to raise the role of institutional investors and improving the transparency of risk disclosure, thereby enhancing investor confidence, improving decision-making, and supporting the increase in firm value.